Tailoring the hyperthermia potential of magnetite nanoparticles via gadolinium ION substitution. Issue 22 (15th November 2021) - Janani, V.; Induja, S.; Jaison, D.; Meher Abhinav, E.; Mothilal, M.; Gopalakrishnan, C.
Abstract: Magnetic nanoparticles are one of the most promising candidates to achieve localization of heat in the region of cancerous tissue. Modified co-precipitation technique is carried out to synthesize Gdx Fe3-x O4 (where, x = 0.00 (IO), 0.04 (IOG02), 0.08 (IOG04), 0.12 (IOG06), 0.16 (IOG08), 0.20 (IOG10). A systematic characterization was performed to study the structural, morphological, elemental, and magnetic properties of the synthesized nanoparticles using X-Ray diffraction (XRD), Field emission scanning microscopy (FESEM), Energy Dispersive Spectroscopy (EDS), Vibrating sample magnetometer (VSM) respectively. The structural analysis revealed the single-phase crystalline nature of magnetite, with the co-existence of secondary phase hematite and goethite beyond x ≥ 0.16. The morphological analysis implied an increase in particle size due to Gd substitution with particle sizes ranging from 7 to 19 nm. Magnetic measurements revealed a magnetic transformation from superparamagnetic nature with magnetic coercivity and remanence to weak ferromagnetic nature upon an increase in the gadolinium content of magnetite. Further, hyperthermia studies showed that with increasing gadolinium concentration, the heating rate, specific absorption rate, and the intrinsic loss power of gadolinium substituted magnetites were increased. The increased specific absorption rate of gadolinium substituted magnetites with low HF factors makes them ideal for clinical hyperthermia applications. Graphical abstract: Image 1